Applying the theory of planned behavior to investigate type 2 diabetes patients' intention to receive injection therapy - Hsu, Su-Han; Tang, Kung-Pei; Lin, Chia-Hui; Chen, Pei-Chun; Wang, Li-Hsuan (Frontiers in Public Health, 2023)
Objectives This study applied the theory of planned behavior (TPB) in shared decision making (SDM) to understand behavioral intention in patients with type 2 diabetes with regard to injection therapy for blood sugar control. Methods A cross sectional study was conducted. 254 patients with type 2 diabetes participated this study and were interviewed by pharmacists in different clinics. A patient decision aid (PDA) entitled “Should I receive injection therapy regarding my type 2 diabetes condition?” was developed for this study and served as interview agenda which comprised 18 items to inquire their willingness to use injection therapy and related considerations during the SDM process. Results The questionnaires were revised using item analysis, exploratory factor analysis, and a criteria of Cronbach’s α > 0.7. This resulted in three constructs for all questionnaires that fit the TPB model. Attitude (β = 0.432; P < .001) and PBC (β = 0.258; P < .001) were directly correlated with intention. TPB explained 35.2% of the variance in intention toward the use of injection therapy. Conclusions Attitude and PBC toward injection therapy positively and significantly influence the patients’ intention to use injection therapy. Practical implications These findings identify a key association for understanding behavioral intention in patients with type 2 diabetes with regard to blood sugar control during SDM.